Side Effects of Brand Ambassadors on Brands “s” - Kuswandi, Ignatius Richard; Kurniadi, Benedicta Alvina; Hundura, Rindina (Ilomata International Journal of Management, 2024)
BTS is a Korean boy band that is internationally renowned, with numerous fans across various countries, especially in Indonesia. BTS collaborates with various brands as brand ambassadors, one of them being Brand "S" brand ambassadors. BTS and ARMY (BTS fans) use various media to communicate with each other, and BTS often posts content related to the brands they collaborate with in their social media. The widely discussed phenomenon among BTS fans revolves around the products offered by the brand "S." The research aims to investigate how word of mouth affects the likelihood of purchasing, using the case study of the boy group BTS as brand ambassadors for the "S" brand. The study involved individuals from the Jabodetabek area who were familiar with the BTS band in association with the "S" brand. The research used a non-probability sampling approach, specifically choosing the convenience sampling technique during the sample selection process. The number of samples used in the study was 122 respondents, and data collection was conducted by distributing questionnaires through Google Forms. The data analysis was conducted using the Structural Equation Modelling (SEM) program SmartPLS 4.0. The results of the study indicate that word of mouth has a positive and significant influence on purchase intention.